Project Change Management Tool - Mat Zin, Mohd Ridzuan (Universiti Teknologi Petronas, 2006)
IT project management especially change management is one ofthe most important element in project management. Project change management is concerning one of the main elements in project management, which is scope. Project change management needs proper documentation due to the nature of the changes which normally take place after business requirement being formulated. Since it is outside the business requirement, change in scope involving financial issues in term of billing for the changes. This project is build aim to tackle change management in IT Project. Change management is one area whereby decide the outcome ofa system. This system will enable project manager to handle change management from registering change request until registering or modifying functionality of system. This project also tackles time and cost management of a project. This project built in web-based application usingASP and MicrosoftAccess2003. Methodology used in developing this project is waterfall methodology. Everything done by flows and revision for every stage needed to ensure the goal ofevery phase achieved. This project also use reference ofother project change management which available in market. Taking advantage of nature of web-based application, this project have quite mobility and accessible as long as there are internet connection available. This make this project reliable in handling project change management process and may give some idea on how Malaysian based project management culture should be absorb into this project in future. IV